2022
DOI: 10.1002/mame.202200640
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐High Loading of Coal‐Derived Flash Graphene Additives in Epoxy Composites

Abstract: Graphene has proved to be an exceptional reinforcing additive for composites, but the high cost of its synthesis has largely prevented its addition on industrial scales. Flash Joule heating provides a rapid, bulk‐scale method for graphene synthesis from coal materials, such as metallurgical coke (MC), into metallurgical coke‐derived flash graphene (MCFG). Here, this work investigates the properties of graphene‐epoxy composites in a higher nanofiller content regime than has previously been reported in literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
(66 reference statements)
0
6
0
Order By: Relevance
“…The flash Joule heating (FJH) method provides a remedy to this through its capability to convert virtually any solid carbon source into turbostratic flash graphene (FG) by a reaction completed in milliseconds or seconds. [1][2][3][4][5][6][7][8][9][10][11] This is performed by discharging a kilojoule-scale electrical pulse through a carbon feedstock to rapidly Joule heat the reactants. The versatility of FJH also permits the synthesis of inorganic complexes, [12][13][14] the extraction of metals from industrial waste, [15,16] and the ultrafast synthesis of various carbon compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The flash Joule heating (FJH) method provides a remedy to this through its capability to convert virtually any solid carbon source into turbostratic flash graphene (FG) by a reaction completed in milliseconds or seconds. [1][2][3][4][5][6][7][8][9][10][11] This is performed by discharging a kilojoule-scale electrical pulse through a carbon feedstock to rapidly Joule heat the reactants. The versatility of FJH also permits the synthesis of inorganic complexes, [12][13][14] the extraction of metals from industrial waste, [15,16] and the ultrafast synthesis of various carbon compounds.…”
Section: Introductionmentioning
confidence: 99%
“…[ 44 ] In epoxy composites, graphene operates as a reinforcing additive, improving toughness through crack bridging and consuming fracture energy by stopping crack formation. [ 45 ] Lubricants and epoxies are commonly used materials that benefit greatly from addition of even small amounts of graphene. The low cost of the FJH process, high quality of the product, and the ready availability of carbon‐containing feedstocks, such as coal, make FG an ideal additive for these lubricant and epoxy roles.…”
Section: Coal‐based Flash Graphenementioning
confidence: 99%
“…8 An external electric field can change the synthesis products, and it has also been suggested that the presence of an electric field can have an effect on the motion of electrically neutral particles. 9 Flash Joule heating (FJH), as a method exhibiting high energy efficiency and an ultrafast heating rate, has recently been used in the synthesis of many materials including graphene, [10][11][12][13][14][15][16] transition metal chalcogenides, 17 and various other carbide and inorganic compounds. [18][19][20][21] It has also been widely explored as a method for effective remediation of soil 22 and battery electrodes 23 as well as a method for recycling and upscaling materials.…”
Section: Introductionmentioning
confidence: 99%